Transforming growth factor β1 antagonizes the transcription, expression and vascular signaling of guanylyl cyclase/natriuretic peptide receptor A – role of δEF1. (5th April 2016) - Sen, Anagha; Kumar, Prerna; Garg, Renu; Lindsey, Sarah H.; Katakam, Prasad V. G.; Bloodworth, Meaghan; Pandey, Kailash N.
Abstract : The objective of this study was to determine the role of transforming growth factor β1 (TGF‐β1) in transcriptional regulation and function of the guanylyl cyclase A/natriuretic peptide receptor A gene ( Npr1 ) and whether cross‐talk exists between these two hormonal systems in target cells. After treatment of primary cultured rat thoracic aortic vascular smooth muscle cells and mouse mesangial cells with TGF‐β1, the Npr1 promoter construct containing a δ‐crystallin enhancer binding factor 1 (δEF1) site showed 85% reduction in luciferase activity in a time‐ and dose‐dependent manner. TGF‐β1 also significantly attenuated luciferase activity of the Npr1 promoter by 62%, and decreased atrial natriuretic peptide‐mediated relaxation of mouse denuded aortic rings ex vivo . Treatment of cells with TGF‐β1 increased the protein levels of δEF1 by 2.4–2.8‐fold, and also significantly enhanced the phosphorylation of Smad 2/3, but markedly reduced Npr1 mRNA and receptor protein levels. Over‐expression of δEF1 showed a reduction in Npr1 promoter activity by 75%, while deletion or site‐directed mutagenesis of δEF1 sites in the Npr1 promoter eliminated the TGF‐β1‐mediated repression of Npr1 transcription. TGF‐β1 significantly increased the expression of α‐smooth muscle actin and collagen type I α2 in rat thoracic aortic vascular smooth muscle cells, which was markedly attenuated by atrial natriuretic peptide in cells over‐expressing natriuretic peptide receptor A. Together, the present results suggest that an antagonistic cascade exists between the TGF‐β1/Smad/δEF1 pathways and Npr1 expression and receptor signaling that is relevant to renal and vascular remodeling, and may be critical in the regulation of blood pressure and cardiovascular homeostasis. Abstract : Atrial natriuretic peptide (ANP) and natriuretic peptide receptor‐A (NPRA) signaling is critical in the regulation of blood pressure and cardiovascular homeostasis. Our results identify novel molecular mechanisms of TGF‐β1‐mediated Npr1 (coding for NPRA) gene repression and receptor signaling suggesting that an antagonistic cascade exists between TGF‐β1/Smad2/3/δEF1 pathways and ANP/NPRA/cGMP system relevant to the renal and vascular functions.